2018
DOI: 10.1002/dneu.22582
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and sex differences in tetramethylenedisulfotetramine (TMDT)‐induced syndrome in rats

Abstract: Tetramethylenedisulfotetramine (TMDT) is a synthetic neurotoxic rodenticide considered a chemical threat agent. Symptoms of intoxication include seizures leading to status epilepticus and death. While children and women have been often the victims, no studies exist investigating the neurotoxic effects of TMDT in developing individuals or females. Thus, we performed such an investigation in developing Sprague-Dawley rats of both sexes in order to identify potential age- or sex-dependent vulnerability to TMDT ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Realistic models of exposure, behavioural assessments and multifaceted treatment investigations are needed to elaborate the toxicity of TETS [ 23 ]. Very recently, Lauková et al [ 24 ] implemented an investigation in developing rats of both sexes to identify any potential age- and sex-dependent vulnerability to TETS exposure. The authors showed that the youngest rats represented the most vulnerable population to the TETS-induced toxidrome.…”
Section: Toxicitymentioning
confidence: 99%
“…Realistic models of exposure, behavioural assessments and multifaceted treatment investigations are needed to elaborate the toxicity of TETS [ 23 ]. Very recently, Lauková et al [ 24 ] implemented an investigation in developing rats of both sexes to identify any potential age- and sex-dependent vulnerability to TETS exposure. The authors showed that the youngest rats represented the most vulnerable population to the TETS-induced toxidrome.…”
Section: Toxicitymentioning
confidence: 99%
“…Irrespective of whether the administration route is oral, subcutaneously or intraperitoneally, the LD 50 in mice or rats is 0.1-0.2 mg/kg with a steep dose-response relationship typically achieving 100% lethality around 0.4 mg/kg (Laukova et al 2019a;Rice et al 2017;Shakarjian et al 2012;Zolkowska et al 2012). Juvenile rats of both sexes are slightly more sensitive to TETS than adult animals (Laukova et al 2018).…”
Section: Introductionmentioning
confidence: 99%